Sex Differences in Hemodynamic and Microvascular Mechanisms of Myocardial Ischemia Induced by Mental Stress. Issue 2 (February 2018) - Sullivan, Samaah; Hammadah, Muhammad; Al Mheid, Ibhar; Wilmot, Kobina; Ramadan, Ronnie; Alkhoder, Ayman; Isakadze, Nino; Shah, Amit; Levantsevych, Oleksiy; Pimple, Pratik M.; Kutner, Michael; Ward, Laura; et al.
Abstract : Objective—: To investigate sex-specific vascular mechanisms for mental stress-induced myocardial ischemia (MSIMI). Approach and Results—: Baseline data from a prospective cohort study of 678 patients with coronary artery disease underwent myocardial perfusion imaging before and during a public speaking stressor. The rate-pressure product response was calculated as the difference between the maximum value during the speech minus the minimum value during rest. Peripheral vasoconstriction by peripheral arterial tonometry was calculated as the ratio of pulse wave amplitude during the speech over the resting baseline; ratios <1 indicate a vasoconstrictive response. MSIMI was defined as percent of left ventricle that was ischemic and as a dichotomous variable. Men (but not women) with MSIMI had a higher rate-pressure product response than those without MSIMI (6500 versus 4800 mm Hg bpm), whereas women (but not men) with MSIMI had a significantly lower peripheral arterial tonometry ratio than those without MSIMI (0.5 versus 0.8). In adjusted linear regression, each 1000-U increase in rate-pressure product response was associated with 0.32% (95% confidence interval, 0.22–0.42) increase in inducible ischemia among men, whereas each 0.10-U decrease in peripheral arterial tonometry ratio was associated with 0.23% (95% confidence interval, 0.11–0.35) increase in inducible myocardial ischemia among women. Results were independent of conventional stress-induced myocardial ischemia. Conclusions—: Women and men have distinct cardiovascular reactivity mechanisms for MSIMI. For women, stress-induced peripheral vasoconstriction with mental stress, and not increased hemodynamic workload, is associated with MSIMI, whereas for men, it is the opposite. Future studies should examine these pathways on long-term outcomes. Abstract : Supplemental Digital Content is available in the text.